Decreased expression of the interleukin 2 receptor on CD8 recipient lymphocytes in intestinal grafts rendered tolerant by liver transplantation in rats. Issue 6 (1st December 1998) - Sarnacki, S; Nakai, H; Calise, D; Azuma, T; Brousse, N; Révillon, Y; Cerf-Bensussan, N
Abstract : Background —In a previous study, it was shown that a spontaneously tolerated DA (RT1a) liver allograft in a PVG (RT1c) recipient was able to induce tolerance of a DA small bowel graft performed 17 days later in spite of infiltration of the intestinal grafts by mononuclear cells. Aims —To compare the phenotype of graft infiltrating cells in rejecting and tolerated small bowel grafts in order to elucidate the mechanism(s) which block the graft infiltrating cells from mediating rejection. Methods —Multiparameter immunofluorescence was used to compare the phenotype and state of activation of donor and recipient cells isolated from intestinal grafts rejected or tolerated after liver transplantation. Results —Three differences were found. Firstly, there was a more rapid replacement of lamina propria (LP) cells by recipient lymphocytes in tolerated than in rejected grafts. Secondly, the proportion of LP recipient CD8αβ+ lymphocytes bearing the high affinity receptor for interleukin 2 was significantly less in tolerated grafts (1.1%, range 0–2%) than in rejected grafts (21.3%, range 9–26%). Finally, tolerated grafts contained significantly less NK lymphocytes (NKR-P1+) and macrophages than rejected intestinal allografts. Conclusions —These observations make it possible to delineate clear cut differences in the phenotype of cells infiltrating rejecting versus tolerated grafts. Furthermore, the data suggest that liver transplantation induces tolerance of intestinal grafts by hampering the activation of recipient TcRαβ+ CD8αβ+ T cells and subsequently the recruitment of non-specific effector cells.